Android Application for Remote Control of Personal Computers - Shynu T; S. Suman Rajest; R. Regin; Steffi. R (Research Parks Publishing LLC, 2023)
The development of mobile devices, particularly in these modern times, has brought about a significant transformation in the way business is conducted. The capability of a mobile phone device is frequently anticipated to be comparable to that of a computer. In this day and age, the majority of people who use mobile phones feel that performing some things on their computers is inconvenient. The majority of people find that switching postures when sitting or stretching not only makes them feel more comfortable, but also makes them feel more at ease when they are browsing through their laptops. Standing five or ten feet away from the computer while being restricted to using only the keyboard and mouse can be an impractical situation. Additionally, the system provides the features to access the files that are available on the computer; if the file appears to be a media file, this Android app can play, pause, stop, mute, and turn on/off full-screen mode of the respective media. As a result, the application that is being proposed is intended to transform the handphone into a wireless keyboard or mouse that also includes a touch pad. The wireless network is the medium through which the link is established (WiFi). It has been demonstrated that this prototype is capable of performing the majority of the functions that are often associated with a computer.